Dust in the centres of galaxies: observations and modelling of dust in the nucleus of NGC1068 and in the galactic centre - Mason, Rachel (The University of Edinburgh, 2003)
As the “archetypal” Seyfert II galaxy, NGC1068 is one o f the best-studied dusty objects in the sky. Yet — in comm on with Seyfert galaxies in general — the properties of its dust are not at all well-known. To remedy this situation I have modelled the IR polarisation and 3.4/rm dust absorption feature observed in the nucleus of NGC1068 and com pared the results with new and existing spectroscopy and polarimetry. I find that to reproduce the observed polarisation, the aligned dust grains in this AGN must be larger than those seen in the Galactic diffuse ISM and molecular clouds. I am also led to conclude that the polarising grains in NG C1068 do not take the form of silicate cores with organic mantles, a model which has been widely used to describe dust in the diffuse ISM of our Galaxy. The organic fraction of the dust instead exists as some form of small, nonpolarising grain, and its 3.4/rm feature shows that it is chemically very similar to carbonaceous dust in other, very different environments. The interpretation of this is not yet clear, but it is consistent with a common formation site and mechanism for the carrier of the band seen in many environments, which is then resistant to processing in the ISM . I have also applied these models to a Galactic centre line of sight, again finding that the core-mantle dust grain model is unlikely to be a valid representation of this dust.